Nature and Roles of Arts Degrees in Contemporary Society : A national scoping project of Arts programs across Australia : project final report. - Gannaway, Deanne (Australian learning and Teaching Council, 2008)
'The project focused specifically on the undergraduate award programs called Bachelor of Arts. It aimed to achieve the following: To understand the nature and role of a Bachelor of Arts degree in contemporary Australia; To map the diverse Bachelor of Arts programs on offer in Australia between 2001-2008; To identify the major strengths, difficulties, capabilities and contributions of the program; and to provide rich base-line data on the nature and models of BAs to be accessible for future curriculum planning for Arts Faculties.' - Executive Summary.